2020
DOI: 10.1111/iju.14229
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cystitis/bladder pain syndrome: The evolving landscape, animal models and future perspectives

Abstract: Abbreviations & Acronyms BPS = bladder pain syndrome CCL2 = C-C motif ligand 2 CNS = central nervous system DMSO = dimethyl sulfoxide EAC = experimental autoimmune cystitis ESSIC = International Society for the Study of BPS FSS = functional somatic syndrome GAG = glycosaminoglycan IC = interstitial cystitis IFN-c = interferon-gamma IL = interleukin MC = mast cell NGF = nerve growth factor OVA = ovalbumin TCR = T-cell receptor TNF = tumor necrosis factor TLR = Toll-like receptor UCPPS = urological chronic pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 145 publications
(191 reference statements)
2
102
0
3
Order By: Relevance
“…In the present study, we explored the clinical characteristics of female should be the first key step in undertaking an overall view of the IC/BPS landscape and in improving patients' management. 6,12,13 Recent clinicopathological and genomic studies suggested that HL-IC is a distinct disease entity from other forms of IC/BPS. 6,8,[13][14][15] neuroimmune abnormalities and/or psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we explored the clinical characteristics of female should be the first key step in undertaking an overall view of the IC/BPS landscape and in improving patients' management. 6,12,13 Recent clinicopathological and genomic studies suggested that HL-IC is a distinct disease entity from other forms of IC/BPS. 6,8,[13][14][15] neuroimmune abnormalities and/or psychosocial problems.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,13 Recent clinicopathological and genomic studies suggested that HL-IC is a distinct disease entity from other forms of IC/BPS. 6,8,[13][14][15] neuroimmune abnormalities and/or psychosocial problems. 6,14,[16][17][18] As well as other studies of various populations and ethnic groups, this study demonstrated that HL-IC patients show distinct bladder-centric clinical features in a Japanese female cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Etiopathogenesis of this heterogeneous entity is quite variable and if there could be a method of grouping or classifying these patients based on clinical clues to the underlying etiopathogensis, then therapies specific to addressing these respective pathogenic mechanisms may be used with good results. 2 The objective of this study was to categorize patients of bladder pain syndrome on the basis of clinical clues towards the possible pathogenic process and apply specific modality for treatment of same.…”
Section: Introductionmentioning
confidence: 99%